2021
DOI: 10.1016/j.plaphy.2020.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Phi class glutathione transferases as molecular targets towards multiple-herbicide resistance: Inhibition analysis and pharmacophore design

Abstract: Multiple-herbicide resistance (MHR) is a global threat to weed control in cereal crops. MHR weeds express a specific phi class glutathione transferase (MHR-GSTF) that confers resistance against multiple herbicides and therefore represents a promising target against MHR weeds. Kinetics inhibition analysis of MHR-GSTFs from grass weeds Lolium rigidum (LrGSTF) Alopecurus myosuroides (AmGSTF) and crops Hordeum vulgare (HvGSTF) and Triticum aestivum (TaGSTF) allowed the identification of the acetanilide herbicide b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 44 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…2.1. Shuffling of Parental GSTF Genes Encoded in A. myosuroides, L. rigidum, T. durum and H. vulgare and Activity Screening Alignment of the parental GSTFs from A. myosuroides, L. rigidum, T. durum and H. vulgare [30,31] showed 88% and 72% sequence homology at the protein and DNA level, respectively. Despite the high homology in primary structures, their kinetics and catalytic properties differ significantly, allowing an interesting research perspective.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2.1. Shuffling of Parental GSTF Genes Encoded in A. myosuroides, L. rigidum, T. durum and H. vulgare and Activity Screening Alignment of the parental GSTFs from A. myosuroides, L. rigidum, T. durum and H. vulgare [30,31] showed 88% and 72% sequence homology at the protein and DNA level, respectively. Despite the high homology in primary structures, their kinetics and catalytic properties differ significantly, allowing an interesting research perspective.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations in our lab [30,31] have shown that the parent enzymes display restricted ligandin function and are able to bind a narrow range of pesticides with high affinity. For instance, chloroacetanilide herbicides appear to bind with high affinity among different families of pesticides [31].…”
Section: Determination Of Butachlor's Half-maximal Inhibitory Concent...mentioning
confidence: 97%
See 3 more Smart Citations